2019
DOI: 10.5551/jat.44834
|View full text |Cite
|
Sign up to set email alerts
|

Coefficients in the CAVI Equation and the Comparison Between CAVI With and Without the Coefficients Using Clinical Data

Abstract: Aim: The Cardio-Ankle Vascular Index (CAVI) is a stiffness index of the arterial tree from the origin of the aorta to the ankle, independent of blood pressure at the time of measurement. The CAVI equation includes the coefficients “a” and “b” to adjust it to the value of Hasegawa's pulse wave velocity, which is compensated for at 80 mmHg of diastolic pressure. To verify this adjustment with the coefficients, the clinical significance of CAVI and CAVI without the coefficients (ha β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 21 publications
0
55
0
3
Order By: Relevance
“…BP at four extremities were then measured by the cuff‐oscillometric method. CAVI was calculated using the following formula, where P sys = SBP, P dia = DBP, ρ = blood density, haPWV is PWV from the origin of the aorta to tibial artery at the ankle through the femoral artery, and a and b are constants to convert the values of CAVI:CAVI=a2ρfalse/)(normalPsys-Pdialn)(normalPsysPdiahaPWV2+b…”
Section: Methodsmentioning
confidence: 99%
“…BP at four extremities were then measured by the cuff‐oscillometric method. CAVI was calculated using the following formula, where P sys = SBP, P dia = DBP, ρ = blood density, haPWV is PWV from the origin of the aorta to tibial artery at the ankle through the femoral artery, and a and b are constants to convert the values of CAVI:CAVI=a2ρfalse/)(normalPsys-Pdialn)(normalPsysPdiahaPWV2+b…”
Section: Methodsmentioning
confidence: 99%
“…Subjects underwent arterial stiffness assessments (VaSera 1500 N, Fukuda Denshi Co., Tokyo, Japan). Left (L-CAVI) and right (R-CAVI) measurements were obtained from the device, CAVI 0 's were converted from CAVI's taking into account CAVI's scale coefficients [8,9]. We prospectively followed participants for a mean of 2.56 years for the composite endpoint of death or heart failure related hospital admission.…”
Section: Methodsmentioning
confidence: 99%
“…It is also interesting to know that the information about CAVI has been recently updated. Takahashi et al [8] showed that the CAVI without the coefficients (coefficients a and b in Equation (1)) is also a valid index of arterial stiffness (Equation (3)). CAVI without coefficients a and b is parameter β, which is referred to as haβ (heart to ankle beta).…”
mentioning
confidence: 99%
“…CAVI without coefficients a and b is parameter β, which is referred to as haβ (heart to ankle beta). Takahashi et al [8] also revealed the coefficient "a" and "b" values that are being used in the CAVI calculation (Table 1). A review of this information raised some interesting discussion about the validity and use of the CAVI index.…”
mentioning
confidence: 99%